PCL‐PEG‐PCL film promotes cartilage regeneration in vivo. (19th September 2016) - Fu, Na; Liao, Jinfeng; Lin, Shiyu; Sun, Ke; Tian, Taoran; Zhu, Bofeng; Lin, Yunfeng
Abstract: Objective: Management of chondral defects has long been a challenge due to poor self‐healing capacity of articular cartilage. Many approaches, ranging from symptomatic treatment to structural cartilage regeneration, have obtained very limited satisfactory results. Cartilage tissue engineering, which involves optimized combination of novel scaffolds, cell sources and growth factors, has emerged as a promising strategy for cartilage regeneration and repair. In this study, the aim was to investigate the role of poly(ε‐caprolactone)‐poly(ethylene glycol)‐poly(ε‐caprolactone) (PCL‐PEG‐PCL, PCEC) PCEC scaffold in cartilage repair. Materials and methods: First, PCEC film was fabricated, and its characteristics were tested using SEM and AFM. Cell (rASC – rat adipose‐derived stem cells, and mASCs – green fluorescent mouse adipose‐derived stem cells) morphologies on PCEC film were observed using SEM and fluorescence microscopy, after cell seeding. Tests of cell viability on PCEC film were conducted using the CCK‐8 assay. Furthermore, full cartilage defects in rats were created, and PCEC films were implanted, to evaluate their healing effects, over 8 weeks. Results: It was found that PCEC film, as a biomaterial implant, possessed good in vitro properties for cell adhesion, migration and proliferation. Importantly, in the in vivo experiment, PCEC film exhibited desirable healing outcomes. Conclusions: These results demonstrated that PCEC film was a good scaffold for cartilage tissue engineering for improving cell proliferation and adhesion and could lead to excellent repair of cartilage defects.